2017
DOI: 10.1177/1687814017717663
|View full text |Cite
|
Sign up to set email alerts
|

Optimal multi-depot location decision using particle swarm optimization

Abstract: The depot locations have a significant effect on the transportation cost in the multi-depot vehicle routing problem. A two-tier particle swarm optimization framework is proposed, in which an external particle swarm optimization and an internal particle swarm optimization are used to determine the optimal depot locations and the optimal multi-depot vehicle routing problem solution, respectively. In the internal particle swarm optimization, a novel particle encoding scheme is used to minimize the computational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A recent survey of metaheuristic algorithms [46] suggests that two of the most common algorithms used for solving MDVRP are Ant Colony Optimization (ACO) and Genetic Algorithm (GA). However, other algorithms like Particle Swarm Optimization (PSO) [58] and Ant Lion Optimization (ALO) [59] have also been successfully applied. GA is a nature-inspired algorithm that is based on the natural selection process.…”
Section: B Multi Depot Vehicle Routing Problem (Mdvrp)mentioning
confidence: 99%
“…A recent survey of metaheuristic algorithms [46] suggests that two of the most common algorithms used for solving MDVRP are Ant Colony Optimization (ACO) and Genetic Algorithm (GA). However, other algorithms like Particle Swarm Optimization (PSO) [58] and Ant Lion Optimization (ALO) [59] have also been successfully applied. GA is a nature-inspired algorithm that is based on the natural selection process.…”
Section: B Multi Depot Vehicle Routing Problem (Mdvrp)mentioning
confidence: 99%
“…11 Shen and Chen used the PSO algorithm to optimize multi-depot location decisions and reduced their average routing distance by approximately 13.16%. 12 Chiou et al investigated a PSO-reinforced fuzzy PID controller for quadrotor attitude control and found that the new elite control parameter gains could be generated and updated rapidly. 13 Chen and Shen used the PSO algorithm to optimize dynamic search control for project scheduling problems and solved an activate operating priority problem and an activate operating mode sub-problem.…”
Section: Introductionmentioning
confidence: 99%
“…These algorithms can use the useful information of the population to find the optimal solution [3]. These efficient and robust algorithms are used to solve a variety of problems, such as path planning [4], economic scheduling problem [5], inverter parameter identification [6], backpack problem [7] and location problem [8]. So far, various researchers have conducted in-depth research on these algorithms, and introduced many naturally-inspired meta-heuristic algorithms, such as particle swarm optimization (PSO) algorithm [9], bacterial foraging algorithm (BFA) [10], artificial fish swarm algorithm (AFSA) [11], artificial bee colony (ABC) algorithm [12], cuckoo search (CS) algorithm [13], bat algorithm (BA) [14], ant lion optimizer (ALO) [15], moth-flame optimization (MFO) algorithm [16], and salp swarm algorithm (SSA) [17], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Operation flowchart of improved grasshopper algorithm.Initialize the swarmX i (i = 1, 2, • • • , n) Initialize c max , c min , R max , R min , G(0), αand maximum number of iterations TCalculate the fitness of each search agent Target = the best search agent while (l < T ) Update c using Eq (8). …”
mentioning
confidence: 99%